창작자 관점에서 본 지역 공연콘텐츠 개발: 평택시문화재단 지역특화 사업 사례 분석 - 이성구; Lee Sung-gu (국제문화예술, 2025)
연구목적: 본 연구는 지역 공연예술 생태계 활성화를 위한 지역특화 사업의 실효성을 검토하고, 창작자 관점에서 공연콘텐츠 개발의 구조적 현실과 과제를 도출하는 데 목적이 있다. 연구방법: 이를 위해 평택시문화재단의 「지역특화 공연콘텐츠 발굴 및 지원」사업과 그 성과물인 뮤지컬 『미스터 테일러』를 사례로 삼아, 기획부터 본공연까지의 제작 전 과정을 질적 사례연구로 분석하였다. 3개년에 걸친 단계별 제작 구조를 중심으로, 창작 실무자 7인을 대상으로 한 심층 인터뷰를 통해 실천적 경험과 인식을 수집하고, 이를 다섯 가지 범주(지역성 구현, 제작 환경, 협업 구조, 유통 가능성, 제도 개선)로 나누어 해석하였다. 연구결과: 단계형 지역특화 사업 지원 구조는 지역 서사의 예술화와 창작자 중심협업 시스템의 가능성을 보여주었으나, 쇼케이스와 본공연 간의 단절, 유통 전략의 부재, 사후 관리의 미비 등이 한계로 지적되었다. 결론: 공연콘텐츠의 자생성과 지속 가능성을 확보하기 위해서는 정책 연계 구조 구축, 창작 초기 단계의 기획 시스템 정비, 후속 유통·재공연 체계 및 관객 개발 전략 마련이 병행되어야 할 것이다. Purpose: This study aims to examine the effectiveness of a local specialized support project for revitalizing the regional performing arts ecosystem and to identify the structural realities and challenges of performing arts content development from the perspective of creators. Methods: To this end, the study analyzes the entire production process―from planning to final performance―of the musical Mr. Taylor, developed through the Pyeongtaek Cultural Foundation’s “Local Specialized Performing Arts Content Support Project.” Using a qualitative case study approach, in-depth interviews were conducted with seven core creators over a three-year, stage-based production structure. The collected data were analyzed through five thematic categories: regionality, production environment, collaborative structure, distribution potential, and policy improvement. Results: The step-by-step regional specialization business support structure showed the possibility of artistic local narratives and a creator-centered collaboration structure, but limitations were pointed out, such as the disconnect between the showcase and the main performance, the absence of a distribution strategy, and the lack of aftercare. Conclusion: In order to secure the autonomy and sustainability of performance content, it is necessary to establish a policy linkage structure, organize a planning system in the early stages of creation, and establish a follow-up distribution/re-performance system and audience development strategy.